2020
DOI: 10.1096/fj.202001808r
|View full text |Cite
|
Sign up to set email alerts
|

Predicting susceptibility to SARS‐CoV‐2 infection based on structural differences in ACE2 across species

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 68 publications
2
40
0
1
Order By: Relevance
“…Our study highlights the importance of banning illegal wildlife trade and consumption, and enforcing the importance of surveilling animals in close contact with humans as potential zoonotic reservoirs to prevent outbreaks in the future. studies have predicted ACE2 orthologs/SARS-CoV-2 S binding affinity or energies but lack of support by virus infection experimentation (16)(17)(18)(19)(20)(21). In this study, we experimentally assessed ACE2 orthologs from a broad range of species for their ability to support SARS-CoV-2 entry.…”
mentioning
confidence: 99%
“…Our study highlights the importance of banning illegal wildlife trade and consumption, and enforcing the importance of surveilling animals in close contact with humans as potential zoonotic reservoirs to prevent outbreaks in the future. studies have predicted ACE2 orthologs/SARS-CoV-2 S binding affinity or energies but lack of support by virus infection experimentation (16)(17)(18)(19)(20)(21). In this study, we experimentally assessed ACE2 orthologs from a broad range of species for their ability to support SARS-CoV-2 entry.…”
mentioning
confidence: 99%
“…The ACE2-lentivirus system was used to introduce amino acid substitutions into mACE2 to identify the amino acids that are responsible for restricting SARS-CoV-2 replication in mACE2-expressing cells. Analysis of crystal structures and species susceptibilities has suggested residues that may be responsible for the differences in binding of the RBD to hACE2 and mACE2 (Alexander et al, 2020; Damas et al, 2020; Griffin et al, 2020; Rodrigues et al, 2020; Wang et al, 2020). Based on these in silico studies, we identified seven residues potentially responsible for the human-mouse differences.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that wild-type mice are generally less susceptible to SARS-CoV-2 infections partly because murine ACE2 does not bind to SARS-CoV-2 as efficiently as hACE2. 22 Accordingly, transgenic mice overexpressing hACE2 in epithelial cells under the control of human cytokeratin 18 (K18) promoter, the K18-hACE2 mice, 23 have been generated and proven more susceptible to SARS-CoV-2 infection, manifested by more exaggerated lung inflammation and injury following intranasal virus inoculation. 23,24 Consistently, we found that lung ACE2 levels were elevated by 1-2 folds in K18-hACE2 mice as compared with gender-and age-matched wild-type C57BL/6 controls (Supporting Information Fig.…”
Section: Rbm-binding Mabs Also Specifically Blocked the Rbm-induced Gmentioning
confidence: 99%